The green corn development and yield on different summer soil covering plants in the organic no-tillage system - Crespo, Aline Marchiori; Souza, Maurício Novaes; Favarato, Luiz Fernando; Guarçoni, Rogério Carvalho; Araújo, João Batista Silva; Rangel, Otacílio José Passos; Souza, Jacimar Luis de; Gonçalves, Dalila da Costa (International Journal of Advanced Engineering Research and Science, 2022)
The objective of this study was to evaluate the growth and yield of green corn cultivated under organic no-tillage system on different ground cover plants. The work was developed in the municipality of Domingos Martins, ES, Brazil (20° 22' 16.91"S and 41° 03' 41.83" W), being arranged in a randomized block design, with six replications and five production systems, consisting of: three soil covers in the organic no-tillage system - with sunn hemp, millet and sunn hemp/millet intercropping; and two systems without straw and with soil tillage - one organic and the other conventional. The double hybrid of corn AG 1051was used, at a spacing of 1.00 x 0.20 m. Evaluations were carried out of stem diameter and plant height, at stagesV5 (five developed leaves), V10 (10 developed leaves) and R3 (milky grains); ear yield with straw and without straw; average weight of 15 ears with straw and without straw; average length and diameter of ears without straw and the percentage of straw. For all agronomic characteristics evaluated, except for length and average diameter of ears without straw and the straw percentage, all the treatments studied were statistically superior to the conventional system treatment. The agronomic characteristic “yield” which is the most important among all evaluated, did not show statistical difference among all treatments under organic system. Therefore, both the organic system without straw and with soil tillage, and the organic systems with straw and without soil tillage using single sunn hemp, single millet and sunn hemp/millet intercropping are possible to be used with good corn yield.